Pemberdayaan Masyarakat Terkait Sampah dengan Prinsip 3R di Kawasan Pantai Desa Adat Jimbaran - I Made Suidarma; Mila Rahayu Damayanti (Jurnal Pengabdian Pada Masyarakat, 2021)
COMMUNITY EMPOWERMENT RELATED TO WASTE WITH 3R PRINCIPLES IN THE JIMBARAN TRADITIONAL VILLAGE BEACH AREA. The traditional village of Jimbaran is a village located in a coastal area. Jimbaran beach is a tourist destination that has strategic potential and attracts tourists to come to visit. The rapid development of the tourism sector has caused various problems, such as environmental pollution due to waste. Plastic waste is the most common waste. This community service aims to provide a little information and knowledge to the community about how to manage waste with the 3R (Reduce, Reuse dan Recycle) principle to create a clean coastal environment and natural conservationt.